Penerapan Aplikasi SATUSEHAT SDMK Bagi SDM Dinas Kesehatan Kabupaten Ponorogo - Zariena Azzren Maizura; Safira Karisma Citra; Titis Purwaningrum (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The SATUSEHAT SDMK platform, developed by Indonesia's Ministry of Health, plays a crucial role in integrating and managing Health Human Resources (SDMK) data across the country. This platform enables healthcare professionals to update their personal and professional profiles and manage practice permits online. This article aims to examine the implementation and optimization of SATUSEHAT SDMK usage for healthcare personnel at the Health Office of Ponorogo Regency. The study involves an analysis of the registration process, practice permit applications, and data validation using SATUSEHAT SDMK, as well as challenges encountered by users at the regional level. The results indicate that using SATUSEHAT SDMK can streamline permit processes and improve the accuracy of healthcare personnel data; however, further optimization is needed, particularly in technical aspects and platform outreach, to enhance its effectiveness among healthcare professionals in Ponorogo Regency.